The effect of an intervention using GIS-generated geo-spatial data on the promotion of spatial cognition and spatial perspective taking in grade 11 learners. Issue 1 (2nd January 2016) - Britz, H.W.; Webb, P.
Abstract : A question asked at the first national conference on the educational applications of geographical information systems (GIS) in Washington 1994, namely what learning does GIS allow that other ways do not and whether teaching GIS at school level is worth the time and effort required to implement it, remains largely unanswered. Literature searches suggest that little has been done to investigate the effectiveness of GIS in education since this question was raised. In investigating what learning using GIS allows that other ways do not, this study tested whether using GIS as a teaching and learning strategy enabled the promotion of learners spatial cognition and spatial perspective taking abilities better than traditional methods such as using atlases, rulers and calculators do. Four secondary Geography teachers in four Port Elizabeth schools volunteered to take part in the experimental aspects of this study. Empirical data on the development of spatial cognition and spatial perspective taking were generated via their grade 11 Geography learners. Experimental and comparison groups of learners wrote three different types of pre- and post-tests where the experimental groups worked on GIS software with geo-spatial data while the comparison groups used traditional methods. The empirical data generated by the learners revealed that GIS software and geo-spatial data do statistically significantly promote better spatial cognition and spatial perspective taking than traditional methods do.